Histological investigation of α-lipoic acid in the wound healing process of diabetic lesions in vivo - Fernandes Teixeira, Guilherme; Rodrigues, Vithoria Régia Teixeira; Saraiva, Andreza Gyslaynny Delmondes; Miranda, Kelvi Wilson Evaristo; Da Silva, Claudio Gleidiston Lima; Pinheiro, Woneska Rodrigues; Sampaio, Luis Rafael Leite (Acta scientiarum. Biological sciences, 2025)
α-Lipoic acid (ALA) is a significant therapeutic agent for inflammation. Understanding the histological parameters involved in the healing process influenced by inflammatory activity is crucial for developing new technologies to treat wounds caused by diabetes mellitus. This study involved diabetic Wistar rats, divided into groups based on treatment: a control group (distilled water and cellulose), a 100 mg.kg-1 dose of α-lipoic acid, and a 200 mg kg-1 dose. Diabetes was experimentally induced, and lesions were created on the rats’ backs. The α-Lipoic acid groups received oral doses of 100-200 mg kg-1, while the control group received distilled water with cellulose. Wounds were later excised and subjected to histological analysis. The 100 mg kg-1 dose exhibited ‘mild’ to ‘absent’ chronic inflammatory responses, while the 200 mg kg-1 dose showed similar results for acute treatments, based on all analyzed parameters. α-Lipoic acid reduced all parameters examined, with the lower dose demonstrating beneficial effects on healing during continuous treatment. In contrast, the 200 mg kg-1 dose yielded results indicating effectiveness in acute treatments. Further studies are required to explore the absorption process of ALA in vivo models.